Identification of Football Talents in U12 – U14 Years in Bangkalan Regency - Kusuma, Andika Akbar; Himawan, Agus; Widodo, Haryo Mukti (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to determine the potential talent of the Dekate FC Football School (SSB) players in the U12–U14 age group in Bangkalan Regency. The method used is quantitative descriptive research with survey techniques and the application of tests and measurements to collect data from a sample of 40 players. The data obtained were analyzed using descriptive statistical techniques to identify the talent categories of the players. The results of the analysis showed that 30 players (75%) were classified as talented, while 10 players (25%) were not talented. The average value (mean) of the entire data is 0.75, with a median and mode value of 1, which indicates that most members of the Dekate FC SSB team have potential talent in the field of football.